Career Aspirations of Potential Applicants for Principals of Catholic Schools: An Australian Perspective - d’Arbon, fms, Tony (Catholic Education: A Journal of Inquiry and Practice, 2006)
Recent surveys of leadership succession planning in Catholic schools in New South Wales, Victoria, South Australia, Tasmania, and the Northern Territory of Australia have confirmed the growing shortage of persons applying for positions of principal in Catholic schools in those states and territory and examined reasons for the decline in numbers. This paper focuses on a particular aspect of that research in which the career aspirations of those being surveyed, in the pool of potential applicants for principal positions, are analyzed and reported. Implications for the future of Catholic schools in Australia as well as for the future leadership of schools in general are examined.